2013
DOI: 10.26719/2013.19.5.447
|View full text |Cite
|
Sign up to set email alerts
|

Second-hand smoke and indoor air quality in public places in Gaza city

Abstract: Second-hand smoke is a major cause of preventable disease and death in the Eastern Mediterranean Region. To assess how second-hand smoke impacts air quality, respirable suspended particles (PM 2.5 ), which are emitted during cigarette and waterpipe smoking, were measured inside and outside of 18 smoking and 5 nonsmoking public venues in Gaza city. Median PM 2.5 level inside the smoking venues was 117 µg/m 3 , which exceeds the WHO guidelines for daily PM 2.5 exposure (25 µg/m 3 ) by more than 4-fold. The media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
(25 reference statements)
1
5
1
Order By: Relevance
“…Recent studies from the Middle East region that used comparable study designs to ours have documented similarly elevated levels of one to two orders of magnitude in venues such as waterpipe cafes compared to those where tobacco smoking was banned. 16,19,20 In contrast, other studies have reported differences between venues that were slightly smaller than those in our study. For example, recent air monitoring in seven cities in the United States found PM 2.5 to be 82% lower in smoke-free hospitality settings than in venues where smoking was permitted.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Recent studies from the Middle East region that used comparable study designs to ours have documented similarly elevated levels of one to two orders of magnitude in venues such as waterpipe cafes compared to those where tobacco smoking was banned. 16,19,20 In contrast, other studies have reported differences between venues that were slightly smaller than those in our study. For example, recent air monitoring in seven cities in the United States found PM 2.5 to be 82% lower in smoke-free hospitality settings than in venues where smoking was permitted.…”
Section: Discussioncontrasting
confidence: 99%
“…9 Exposure to ETS from waterpipes, which are typically smoked in social settings, including cafes, bars, and restaurants, may be of particular concern for workers in such establishments, who often have low levels of protection due to inadequate smoking regulations in some countries. 1016 The World Health Organization's Framework Convention on Tobacco Control calls on governments to ‘protect all persons from exposure to tobacco smoke’, rather than just specific populations such as children or pregnant women. This protection should be extended, according to Article 8 to, ‘indoor workplaces, public transport, indoor public places and…other public places’.…”
mentioning
confidence: 99%
“…Moreover, Hammal et al 34 observed mean indoor PM 2.5 levels of 264 μg/m 3 arising from the use of tobacco-free ‘herbal’ WP products. The particulate matter levels detected among WP cafes in Qatar also compare closely with those observed in non-smoke-free public venues (predominantly containing cigarettes) reported elsewhere in the EMR, and throughout the world 21 28 35 36…”
Section: Discussionsupporting
confidence: 76%
“…We did not identify many significant associations between venue characteristics and SHS levels. Other studies of SHS in waterpipe tobacco venues have reported positive associations between smoker density and mean PM 2.5 (Abuelaish et al, 2013; Al Mulla et al, 2014; Cobb et al, 2013; Saade et al, 2010; Zaidi et al, 2011; Zhang et al, 2013). …”
Section: Discussionmentioning
confidence: 82%
“…Environmental Protection Agency, 2013; World Health Organization, 2014). Other studies of waterpipe tobacco venues in the US (Cobb et al, 2013; Fiala et al, 2012; Zhang et al, 2013; Zhou et al, 2014), Qatar (Al Mulla et al, 2014), Lebanon (Saade et al, 2010), Pakistan (Zaidi et al, 2011), and Palestine (Abuelaish et al, 2013) have all found elevated PM 2.5 concentrations, with mean concentrations ranging from 117 μg/m 3 to 1,419 μg/m 3 .…”
Section: Discussionmentioning
confidence: 95%